An Evaluation of AES-256 Based PDF Document Security Using Cryptographic Metrics and Blockchain Based Hash Storage - Ellen Chandra; Nur Rochmah Dyah Puji Astuti (Scientific Journal of Informatics, 2026)
Purpose: This research aims to design and implement a digital document security by integrating the Advanced Encryption Standard (AES) 256-bit algorithm with blockchain technology to protect documents from manipulation, forgery, and information leakage. Methods: The study involved implementation using Python. AES-256 was applied to encrypt digital documents, while the hash value of the ciphertext was stored on the blockchain to ensure integrity and authenticity. System performance was evaluated through avalanche effect testing, entropy analysis, and process time measurement. Result: The average efficiency is 49.989% for small documents, 49.988% for documents 50-200 KB and 49.998% for documents larger than 200 KB, using good bits. An average entropy value of 7.99 indicates a high performance. The average sending time is 1.62 ms, and the average blockchain sending time is 1061.862 ms making it possible to send in sending digital documents. Novelty: This study integrates AES-256 encryption with blockchain-based hash storage to simultaneously ensure confidentiality, integrity, and authenticity of digital documents with high efficiency.